Induced-seismicity geomechanics for controlled CO2 storage in the North Sea (IGCCS). (March 2022) - Park, Joonsang; Griffiths, Luke; Dautriat, Jérémie; Grande, Lars; Rodriguez, Ismael Vera; Iranpour, Kamran; Bjørnarå, Tore I.; Moreno, Héctor Marín; Mondol, Nazmul Haque; Sauvin, Guillaume; Sarout, Joel; Soldal, Magnus; et al.
Highlights: Micro-seismic monitoring of CO2 storage in the North Sea. Geomechanics material models relevant for CO2 storage in the North Sea. Acoustic emission test upscaled to field micro-seismic data. Advanced coupled THM numerical simulation of CO2 injection procedure considering temperature and fluid types. New insights on micro-seismic acquisition system. Abstract: The aim of the current study, IGCCS (2017–2020), is to evaluate the feasibility of micro-seismic (MS) monitoring of CO2 injection into representative storage candidates in the North Sea, based on broad and quantitative characterization of relevant subsurface behavior with respect to geology, geomechanics and seismicity. For this purpose, we first group potential CO2 storage sites in the North Sea into three different depths. Then, advanced triaxial rock mechanical tests are performed together with acoustic emission (AE) acquisition under representative loading for CO2 storage sites in the North Sea and for formations of each depth group, covering shale, mudstone and sandstone cores. Our work focuses particularly on quantifying the effects of injected fluid type and temperature on mechanical behavior and associated MS response of subsurface sediments. The experiment results show that each depth group may behave differently in responses to CO2 injection. Particularly, the occurrence of detectable MS events is expected to increase with depth, as the combined effects of rock stiffness and temperature contrast between the host rock and injected CO2 are increasing. In addition, lithology plays an important role in terms of the MS response, i.e. high AE event rate is observed in sandstones, while aseismicity in shale and mudstone. The test results are then scaled up and applied to advanced coupled flow-geomechanics simulations and a synthetic field-scale MS data study to understand micro-seismicity at fracture, reservoir and regional scales. The numerical simulation of scCO2 injection scenario shows quite different stress-strain changes compared to brine injection, resulting mainly from the thermally-induced behavior. Furthermore, the numerical simulation study via so-called Cohesion Zone Modeling (CZM) approach shows strong potential to improve our understanding of the multiphase-flow-driven fracture propagation. Our synthetic MS data study, focused on slow-earthquake scenario, also suggests that sensors with high sensitivity at low frequency might be necessary for better signal detection and characterization during CO2 injection. This manuscript covers the main findings and insights obtained during the whole study of IGCCS, and refers to relevant publications for more details.